Estrutura genética, dinâmica populacional e demografihistórica do tamanduá-bandeira Myrmecophaga tridactyla Linnaeus, 1758 (Pilosa: Myrmecophagidae) - Raphael Teodoro Franciscani Coimbra (2017)
The giant anteater (Myrmecophaga tridactyla Linnaeus, 1758) is the largest of all current anteater species and ranges from Honduras to northern Argentina, inhabiting from moist and deciduous forests to savannas and grasslands. The species is constantly threatened by poaching, habitat loss and fragmentation, wildfires and road kills, and its population numbers are declining. Currently, it is likely extinct in Belize, El Salvador, Guatemala and Uruguay. Therefore, M. tridatyla is listed as vulnerable by IUCN and integrates the CITES Appendix II. In Brazil, the giant anteater is possibly extinct in the states of Rio Grande do Sul, Santa Catarina, Rio de Janeiro and Espírito Santo. Additionally, a few areas harbor large populations of the species, such as the Emas and the Serra da Canastra National Parks, both located in the Cerrado. However, this biome is threatened by the expansion of agricultural lands, livestock and production of charcoal. Hence, the Brazilian Ministry of Environment also lists M. tridactyla as vulnerable. A previous study on Brazilian populations of giant anteaters found evidences of both population structure and expansion. Here, we investigate the geographic patterns of genetic diversity, gene flow dynamics and historical population size changes in the species’ populations in Brazil. We analyzed 2854 bp of mitochondrial and nuclear sequences of 106 individuals from Cerrado (CE), Pantanal (PT), and both Amazon (AM) and Atlantic Forests (AF). We constructed haplotype networks, performed both a Bayesian clustering analysis and an analysis of molecular variance, and calculated the haplotype and nucleotide diversities. Furthermore, we estimated rarefied/extrapolated haplotype richness curves and carried out both migration model selection and demographic reconstruction. The analysis of mitochondrial DNA confirmed the existence of two distinct genetic clusters (φST = 0.3275): one in the AM biome, cluster [AM]; and another in the CE, PT and AF biomes, cluster [CEPTAF]. The mitochondrial haplotype diversity observed for the species (h = 0.7623) was moderate when compared to other threatened and non-threatened species. At the population level, the mitochondrial haplotype richness showed a trend to be higher in [CEPTAF] than in [AM], probably due to a smaller effective population size for the latter. We found gene flow from [AM] to [CEPTAF], possibly due to both greater food availability and M. tridactyla‘s preference for heterogeneous habitats found in both CE and PT. We also recovered a ~ 7.5-fold increase in population size since 60 kya and discussed hypotheses for its causes. In conclusion, we demonstrated the influence of ecological characteristics of M. tridactyla on both the natural history and genetic diversity configuration of its populations, reinforcing the importance of the CE for the species’ conservation.